Justice in Post-Conflict Settings: Islamic Law and Muslim Communities as Stakeholders in Transition - Zoli, Corri; Bassiouni, M. Cherif; Khan, Hamid (Utrecht Journal of International and European Law, 2017)
This essay is one of the first collaborative efforts to identify the underlying norms embedded in diverse traditions of Islamic law as these apply to contemporary Muslim communities experiencing conflict or transitioning from conflict. This long overdue endeavor draws upon comparative legal analyses, postconflict justice traditions, global governance, and empirical conflict studies to explore why Islamic legal norms are not often used as a resource for restraint and guidance in contemporary conflict settings. In exploring this puzzle, the authors make the case for strengthening commensurate Islamic and international conflict norms for complex conflicts and postconflict tradition. We also situate Islamic postconflict justice norms—which are too often confined to religious and natural law discussions—into contemporary problems of security policy, conflict prevention, and problems of governance. We indicate the many benefits of such a comparative approach for citizens of diverse Muslim and Arabs states and communities, trying to build pathways out of conflict, and for humanitarian and human rights practitioners working in such arenas toward similar goals. An additional, important benefit in excavating such shari’a norms is in providing the intellectual basis to counter politicized, extremist, and instrumentalist uses of Islamic law to justify extreme uses of political violence across the Middle East, Central and South Asian, and African regions.